Social Media and General Elections in Malaysia 2018 and Indonesia 2019 - Dani Fadillah; Luo Zheng Lin; Dong Hao (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2019)
In 2018 and 2019, Malaysian and Indonesian eligible voters cast their ballots  for prime minister and president and vice president respectively.  Especially in Indonesia, the eligible voters also  elected members of the Regional Representative Council,   the  House of Representatives,  Provincial Legislative Council and District/Municipal Legislative Council. Prior to the polls, the issue of who would run for presidency and vice presidency had become a hot and interesting topic of conversation among Indonesian citizens, with many of them using social media to express it. However, when the society talked too much about politics on the cyber media, the problem is whether they could come up with constructive rather than destructive content of discussion without destroying democracy.  The methodology of this research is library research in which the author collected a number of library materials containing in-depth study of a subject, and found relevant keywords in the catalogs, indexes, search engines, and various scientific journals. The newer the sources, the more up-to-date references and quotations will be.  To search a database effectively, the author started the search by finding keywords, seeking relevant records, and then narrowing  the keywords to focus on the search. The author later evaluated carefully each source found.